The Association of Religiosity, Sexual Education, and Parental Factors with Risky Sexual Behaviors Among Adolescents and Young Adults - Haglund, Kristin A. (Journal of religion and health, 2010)
This study examined the association of religiosity, sexual education and family structure with risky sexual behaviors among adolescents and young adults. The nationally representative sample, from the 2002 National Survey of Family Growth, included 3,168 women and men ages 15-21 years. Those who viewed religion as very important, had frequent church attendance, and held religious sexual attitudes were 27-54% less likely to have had sex and had significantly fewer sex partners than peers. Participants whose formal and parental sexual education included abstinence and those from two-parent families were 15% less likely to have had sex and had fewer partners.